Effects of job satisfaction and demographic factors on organizational commitment in public and private sectors - Bayram, Hande (My University, 2001)
Tezimde İş Tatmini ve İşe Bağlılık konularını inceledim. Buradaki amaç iş tatmini ve faktörlerinin (maaş, işin kendisi gibi) ve kişisel özelliklerin (yaş, cinsiyet,eğitim,medeni durum gibi) işe bağlılık üzerindeki etkisini özel ve kamu sektöründe değişik açılardan incelemekti İş Tatmini ve İşe Bağlılık çoğu zaman bilimadamları, sosyologlar ve birçok psikolog tarafından ilgi çeken ve incelenen konular olmuşlardır. Sadece iş tatmini ile ilgili üç bin çalışma yapılmıştır. Tezimde, İşe Bağlılık Anketi, İş Tatmini Anketi ve Kişisel Bilgi Formları Kuzey Kıbrıs Ekonomi ve Maliye Bakanlığı, Telsim ve Turkcell'e dağıtılarak 165 çalışan bu anketlere katılmıştır. Tezin ilk aşaması iş tatmini ve işe bağlılık için yapılan literatür taramasıdır. Literatür taramasından sonra teorik iskelet hazırlanmış ve tezde kullanılan methodoloji anlatılmıştır. Methodoloji kısmı hipotezler ve sorular, tez için seçilen grubun özellikleri, grubun tanımı ve büyüklüğü, iş tatmini anketi, işe bağlılık anketi, kişisel bilgi formu ve son olarak toplanan verilerin analizini ve bu analizde kullanılan metodları içermektedir. En son kısımda ise sonuç ve görüşler kısmı yeralmaktadır. Sonuç olarak gördüm ki, iş tatmini ve işe bağlılık arasında direk olarak bir ilişki bulunmamaktadır. Aynı zamanda yaş, eğitim, toplam çalışılan yıl, medeni durum gibi kişisel faktörlerin de işe bağlılık üzerinde bir etkisi gözlemlenememiştir. Bu sonuçlara ek olarak, özel ve kamu sektöründe çalışan kişilerin işe bağlılık oranındada bir farklılık bulunmamıştır. Sadece iş tatmininin bir faktörü olan işin kendidi faktorünün işe bağlılık üzerinde direk etkisi gözlemlenebilmiştir. Fakat iş tatmini ile ilgili sonuçlarda farklılıklar gözlemlenmiştir.Toplam çalışılan yıl ve bir işyerinde toplam çalışılan yılın iş tatmini üzerinde etkisi olduğu gözlemlenmiştir. Aynı zamanda özel ve kamu sektöründe çalışmakta iş tatmini üzerinde etkisi olan bir faktör olarak gözlemlenmiştir.

In this thesis I am interested with two components such as job satisfaction and organizational commitment. The purpose of the study is to analyze the effects of job satisfaction and its factors (such as work itself, pay, promotion, etc.) and demographic variables (such as age, gender, education, etc.) on organizational commitment in several aspects. Job satisfaction and organizational commitment receive considerable attention from industrial and organizational psychologists, management scientists and sociologists. Three thousands studies had been done on job satisfaction alone . Much of the interest in analyzing job satisfaction and organizational commitment stems concern for the behavioral consequences that are hypothesized to result from job satisfaction and/ or organizational commitment. Organizational Commitment Questionnaire, Job Satisfaction Questionnaire and Demographic Form were given to Ministry of Finance and Economics of Turkish Republic of Northern Cyprus (Public) and Telsim (Private) and Turkcell (Private) personnel. 165 employees answered these questionnaires. First step of this thesis was literature survey of job satisfaction and organizational commitment. After literature survey theoretical framework was done and methodology used in this thesis will be explained. Methodology part includes information about hypotheses and questions, sampling definition, sampling method, sample size, sample characteristics, job satisfaction questionnaire, organizational commitment questionnaire, demographic information form and finally analysis of data and methods used to analyze collected data. And final section will be the results and discussion part. As a result, I saw that there is not significant and direct relationship between job satisfaction and organizational commitment. Also demographics factors such as age, gender, education, marital status and total working years had no direct relationship with organizational commitment. Addition to these results, there is not any relationship between sectors (such as public and private) and organizational commitment. Only job satisfaction factor work itself had a significant and positive relationship with organizational commitment. But when I looked at the relationship between job satisfaction and demographic factors, results were different. Because total working years and total working years in a particular organization had a great impact on job satisfaction. Also results showed that working in private sector and working in public sector made a difference on job satisfaction.
Keywords: İŞ TATMİNİ; İŞE KATILMA